2020
DOI: 10.1038/s41467-020-15140-z
|View full text |Cite
|
Sign up to set email alerts
|

2,6-Diaminopurine as a highly potent corrector of UGA nonsense mutations

Abstract: Nonsense mutations cause about 10% of genetic disease cases, and no treatments are available. Nonsense mutations can be corrected by molecules with nonsense mutation readthrough activity. An extract of the mushroom Lepista inversa has recently shown highefficiency correction of UGA and UAA nonsense mutations. One active constituent of this extract is 2,6-diaminopurine (DAP). In Calu-6 cancer cells, in which TP53 gene has a UGA nonsense mutation, DAP treatment increases p53 level. It also decreases the growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 62 publications
5
65
0
Order By: Relevance
“…Recently, it was reported that clitocine and 2,6-diaminopurine, found in extracts from the mushroom Lepista inversa , have a significant nonsense suppression activity [ 61 ]. More specifically, 2,6-diaminopurine could allow UGA PTCs to be read as a tryptophan codon [ 62 ]. As with all small-molecule nonsense suppressors, it needs to be determined whether the amino acid incorporated at the PTC will render a full-length functional protein.…”
Section: Suppression Of Nonsense Mutations: Approaches and Challenmentioning
confidence: 99%
“…Recently, it was reported that clitocine and 2,6-diaminopurine, found in extracts from the mushroom Lepista inversa , have a significant nonsense suppression activity [ 61 ]. More specifically, 2,6-diaminopurine could allow UGA PTCs to be read as a tryptophan codon [ 62 ]. As with all small-molecule nonsense suppressors, it needs to be determined whether the amino acid incorporated at the PTC will render a full-length functional protein.…”
Section: Suppression Of Nonsense Mutations: Approaches and Challenmentioning
confidence: 99%
“…While PTCs do promote translation termination, they are more sensitive to readthrough than physiological stop codons. Although several studies using readthrough molecules have shown the absence of readthrough at physiological stop codons (Welch et al ., 2007; Benhabiles et al ., 2017; Trzaska et al ., 2020), it remains necessary to demonstrate for each new molecule that it does not impact translation termination at physiological stop codons.…”
Section: Different Types Of Stop Codon Readthroughmentioning
confidence: 99%
“…It seems, however, that this is not an absolute rule, as some readthrough activators with no NMD‐inhibiting action promote greater synthesis of full‐length proteins than do dual‐action molecules. For instance, the readthrough activators Lepista flaccida extract H7 and 2,6‐diaminopurine, which do not inhibit NMD, correct UGA and UAA (extract H7) or UGA only (2,6‐diaminopurine) more effectively than dual‐action G418 (Correa‐Cerro et al ., 2005; Benhabiles et al ., 2017; Trzaska et al ., 2020).…”
Section: Parameters Influencing Stop Codon Readthroughmentioning
confidence: 99%
See 2 more Smart Citations